2021
DOI: 10.1080/0309877x.2021.1986622
|View full text |Cite
|
Sign up to set email alerts
|

(Re)conceptualising effective teaching in further education: an exploratory study

Abstract: Government-led reforms in the Further Education (FE) sector in the UK have highlighted the impact that FE institutions can have on national productivity and economic growth. This has resulted in growing calls to support the performance of FE teachers in the classroom. There is a paucity of research that has considered effective teaching practice within the unique context of FE. To address this gap, we sampled 90 full-time FE teaching staff, who participated in one of 12 in-depth focus groups, which aimed to: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…The lack of research on the FE sector is surprising given the FE sector has been subject to major changes in recent years [17], and has been highlighted as playing a pivotal role by the English government in developing the next generation of employees with the right computing and digital skills for the future [30,47]. Furthermore, there are calls to support the performance of FE lecturers [88], and so effective CPD for CS teachers can help achieve these goals. However, the subject specialist elements of initial teacher training for FE lecturers has been weak [72], there are recruitment difficulties [5,30], and there are challenges preventing CS teachers taking part in CPD such as a lack of funding [4,14], a lack of time [92], and a heavy workload [72].…”
Section: The Problem and Potential Solutionmentioning
confidence: 99%
“…The lack of research on the FE sector is surprising given the FE sector has been subject to major changes in recent years [17], and has been highlighted as playing a pivotal role by the English government in developing the next generation of employees with the right computing and digital skills for the future [30,47]. Furthermore, there are calls to support the performance of FE lecturers [88], and so effective CPD for CS teachers can help achieve these goals. However, the subject specialist elements of initial teacher training for FE lecturers has been weak [72], there are recruitment difficulties [5,30], and there are challenges preventing CS teachers taking part in CPD such as a lack of funding [4,14], a lack of time [92], and a heavy workload [72].…”
Section: The Problem and Potential Solutionmentioning
confidence: 99%
“…Правительственные реформы в секторе дополнительного образования (FE) в Великобритании выявили влияние, которое учреждения FE могут оказать на национальную производительность и экономический рост. Это привело к растущим призывам поддержать работу учителей FE в классе [30].…”
Section: Introductionunclassified
“…In addition, Smothers N et al argued that characteristics such as expertise, teaching skills, personal qualities and interpersonal qualities are expected of effective PE teachers and found through their study that conceptualizing teacher effectiveness can potentially support FE teacher training and development [16]. Jacob R et al investigated the impact of training on teachers' teaching to improve their mathematics teaching through this study for a comparative experiment, and the results showed that training could improve teachers' mathematical knowledge without affecting teaching practices and student achievement [17].…”
Section: Introductionmentioning
confidence: 99%